Regional Differences in Spatiotemporal Drought Characteristics in Great Britain - Tanguy, Maliko; Haslinger, Klaus; Svensson, Cecilia; Parry, Simon; Barker, Lucy J.; Hannaford, Jamie; Prudhomme, Christel (Frontiers in Environmental Science, 2021)
Despite being one of the most damaging natural hazards, droughts and their spatiotemporal dynamics are typically not well understood. Great Britain, which is the focus of this work, has experienced many major drought episodes in the past, causing a range of socioeconomic and environmental impacts. Here, we apply a recently developed technique to identify and characterise past droughts, using space-time connectivity to extract events from a monthly gridded precipitation dataset covering 1862–2015, without imposing fixed geographical boundaries or time-frames. For each grid cell, the data was aggregated into four new time series using moving averages over 3-, 6-, 12- and 24-month windows. These reflect a range of response times for different types of drought impacts. Drought events were then extracted for each time window separately. In order to assess regional differences in drought characteristics, each extracted drought was assigned to one of three regions: the South-East (SE), the North-West (NW) and a “Transition” region in-between them. A frequency analysis of drought characteristics (duration, area, intensity and severity) highlighted differences between regions: for short and medium accumulation periods (3, 6, and 12 months), short and less severe droughts are more frequent in the NW than in the SE, whereas long, spatially extended and more severe droughts are more frequent in the SE than in the NW. However, for long accumulation periods (24 months), fewer differences are observed between the NW and the SE. In the “Transition” region, severe droughts are less frequent than in the other two regions. A timeline of historic drought events detected by our method included the vast majority of known drought events from previous studies, with a few additional ones, and we shed important new light on the relative severity of these historical drought episodes. Finally, an analysis of the spatial coherence between regions showed that the most extreme drought events presented little spatial coherence, whereas less severe droughts tend to be more spatially coherent. This has important implications for water resources planning and drought management strategies, particularly given the increasing emphasis on inter-regional water transfers as a potential solution in situations of extreme drought.